The Influence of Work Dicipline and Teamwork on The Performance of Assembling Departement Employees at PT Adis Dimension Footwear Tangerang Regency - Eva, Nur; Fahmi, Khaerul; Setiawan, Temmy (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to determine: (1) the partial effect of work discipline on employee performance; (2) the partial effect of teamwork on employee performance; (3) the simultaneous effect of work discipline and teamwork on employee performance.This study uses a quantitative descriptive method, which describes variables as they are, supported by numerical data generated from actual conditions. The population in this study was all employees in the Assembly division at PT. Adis Dimension Footwear Balaraja-Tangerang. The research sample consisted of 57 respondents, and the technique used to determine the sample in this study was simple random sampling. Meanwhile, to determine the representative sample size in quantitative research, the Slovin formula was used. Data analysis used multiple linear regression analysis with SPSS 26.The results of this study indicate that (1) partially, work discipline significantly influences the performance of employees in the Assembly division at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value> t table (4.141>2.005) and a significance value of 0.000 smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (2) Partially, teamwork significantly influences the performance of Assembling department employees at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value> t table (2.448>2.005) and a significance value of 0.015 smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (3) Simultaneously, work discipline and teamwork significantly influence the performance of Assembling department employees at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by F count> F table (13.014>3.17) with a significance level of 0.000. Thus Ha is accepted and H0 is rejected.Based on the research results, it can be concluded that the variables of work discipline and teamwork, both partially and simultaneously, have a significant influence on the performance of employees in the Assembling department at PT. Adis Dimension Footwear Balaraja-Tangerang.